(untitled) (Journal of the College of Education for Women, 2019)
This study aims to create spatial balance between two Iraqi writers’ novels (MaysaloonHadi, Alya Talib) technical and objective illustrates similarity points and difference in thewriters’ style. We depended in our research on spatial classification considering the aggressiveand friendly, since the writers focused on them.The research study concluded to many sides, some of which are similar and some aredifferent. Firstly, ingenuity description of the writers. Followed by the deep connection theyhave. Because of the personal experience it emanated from alienation sensations and nostalgiato deep roots to homeland.On the other hand, difference aspects, we see Maysaloon takes symbols and illusionsunlike Alya which was her style close to smooth and empty from deception. The character ofprevailing on (Shai Al-Aroos) novel is objectively, while we see Alia is moving tosubjectively, Maysaloon focused on central character while showing personal same writerwith Alia Talib. It is a documentary novel.